The Effect of Reporting Convergence toward an Integrated Framework on Financial Reporting Quality and Agency Conflicts - Hassan Badri Gamchi; Mohammad Hassani; Ahmad Yaghoobnezhad; Ehsan Rahmaninia (بررسی‌های حسابداری و حسابرسی)
ObjectiveThere are always incentives for agency problems in firms due to potential conflicts of interest among managers, shareholders, and stakeholders. Therefore, efforts to disclose appropriate and high-quality information are one of the approaches to reduce agency conflicts. Since integrated reporting is viewed as a future-oriented approach, it is crucial to assess the potential consequences of adopting an integrated reporting framework on financial reporting quality, taking agency motives into account This research analyzed the impact of the level of reporting convergence toward an integrated framework on financial reporting quality and agency conflicts.MethodsTo measure reporting convergence toward integrated reporting, a checklist was used that was designed based on the international integrated reporting framework. The integrated reporting framework is principles-based. The purpose of this framework is to establish guiding principles and content elements that govern the overall content of an integrated report. The guiding principles underpin the preparation and presentation of an integrated report, informing the content and how information is presented, while the content elements provide details of the information to be reported. Earnings quality, as a proxy for financial information quality, was assessed based on the inverse absolute value of residuals' standard deviation derived from an accrual model at the firm level. Agency cost, as a proxy for conflict of interest, was measured using an efficiency criterion based on the ratio of operational expenses to operational revenues. The research population includes 144 firms listed on the Tehran Stock Exchange over seven years from March 2016 to March 2023. Multivariable panel regression models, based on firm-year observations, were used to test the research hypotheses.ResultsThe findings showed that an increase in convergence level toward an integrated reporting framework improved earnings quality and reduced agency costs. Additionally, although agency costs reduced earnings quality, information disclosure based on integrated reporting mitigated this effect, thereby improving reported earnings quality. Firms that have a higher level of information disclosure following the integrated reporting framework use fewer earnings management tricks and exhibit higher earnings quality. Furthermore, the impact of implementing integrated reporting on earnings quality can be influenced by agency costs. Integrated reporting, as a superior information disclosure mechanism, strongly relates to financial information quality in firms facing agency costs. The effectiveness of integrated reporting is more pronounced in firms with agency problems.ConclusionThe results indicated that the improvement in transparency and completeness of information disclosure, due to the reporting convergence toward an integrated framework, increases financial information quality, especially earnings quality, over time. In addition, focusing on the benefits of integrated reporting mitigates agency conflicts and reduces agency costs. Acceptance of new reporting approaches requires studying their dimensions and possible future consequences. Since the movement toward an integrated reporting framework in Iran is not accompanied by specific requirements, it is suggested to analyze the challenges, opportunities, threats, drivers, barriers, and consequences of the integrated reporting approach by focusing on the information needs of interested groups.